Sporadic Hemiplegic Migraine Type 1 and Congenital Ataxia due to a Single Amino Acid Deletion (ΔF1502) in CACNA1A: A Challenging Diagnosis - Albamonte, Emilio; Barp, Andrea; Duga, Valentina; Carraro, Elena; Passarini, Alice; Bergamoni, Stefania; Maggi, Lorenzo; Sansone, Valeria Ada (Journal of Pediatric Neurology, 2021)
Mutations in the CACNA1A gene have been classically related to three neurologic disorders: hemiplegic migraine type 1 (both familiar and sporadic FHM1/SHM1), episodic ataxia type 2 (EA2), and spinocerebellar ataxia type 6 (SCA6). More recently, pathogenic variants in CACNA1A have been recognized as causative of an early-onset cerebellar syndrome consistent with the definition of congenital ataxia (CA), variably associated with paroxysmal symptoms. Early recognition of congenital ataxia is challenging because the presenting symptoms, such as hypotonia, weak deep tendon reflexes, and delayed motor milestones, are unspecific while clear signs of a cerebellar syndrome which are usually not seen before the second or third year. Here, we report on a case of nonepisodic ataxia of congenital onset and severe SHM1 where the diagnosis of congenital ataxia was made retrospectively after the identification of the ΔF1502 pathogenic variant in CACNA1A by an hemiplegic migraine multigene panel, conducted for the onset of hemiplegic migraine attacks associated with hemispheric swelling. A significant reduction in migraine attacks frequency was achieved with acetazolamide.
Keywords: CACNA1A; hemiplegic migraine; congenital ataxia; childhood hypotonia